On Nepalese English Discourse Granting Citizenship to English in Nepal via Corpus Building - Karn, Sajan Kumar (Journal of NELTA, 2012)
The adoption and adaptation of the English language across the globe have given birth to several nativized varieties such as Indian English, Japanese English, Singaporean English etc. A good number of papers have appeared to argue that a divergent variety of English has grown in Nepal with its own distinctive features at all language levels. The emergence and growth of new English in Nepal, however, have generated heated debates amongst scholars. Whereas some argue that English should be owned and promoted for it has become an inevitable component of not only Nepalese academia but also socio-political life, others fear the development as fatal to indigenous linguistic and cultural heritages. In this article, I propose to own Nepalese English but cautiously i.e. the way it does not ruin our local inheritances. Nonetheless, I primarily advocate building a corpus of Nepalese English to authenticate it and pave the way for owning DOI: http://dx.doi.org/10.3126/nelta.v16i1-2.6127 NELTA 2011; 16(1-2): 30-41